Analisa Perlindungan Hak Pekerja Perempuan pada Pegawai Dinas Transmigrasi dan Tenaga Kerja - Amanda Eliza; Sudarman Sudarman (Journal of Social and Policy Issues, 2021)
This study aims to analyze the fulfillment of the rights of women workers at the Department of Transmigration and Manpower. The rights of women workers are the focus of the research, because the rights of women workers should be fulfilled by the government to provide protection for women workers. The research method used in this study uses a qualitative method with a descriptive approach to answer the research problem. Research analysis techniques used are interviews, observation and documentation, triangulation and combinations. as well as regulations governing the protection of the rights of women workers. The conclusions obtained based on the research conducted in the research have applied regulations related to the protection of women's workers' rights to employees of the Transmigration and Manpower Office. In this case, the employee has received special rights for female employees as regulated in the labor law.